Assessment of Early Intervention Services to Better Child Outcomes among Part C Infants and Toddlers - Brendan Ibe; Tiffany Fowles; Seema Csukas; Jackie Conner; Grace Kelley; Donna Johnson; Cynthia Bryant; Michelle Allen (Georgia Southern University, 2016)
Background: Early intervention services have been shown to improve child outcomes. Rapid proliferation of neural connections and circuits contribute to the rapid growth of the brain in the first three years of life. These neural circuits which create the foundation for learning are most flexible in this period and become increasingly more difficult to change thereafter. The purpose of this study is to examine the relationship between early enrollment in Georgia's Part C birth to three early intervention program and improved child outcome ratings upon exiting the program at 3 years of age. The study used 2013 & 2014 Annual Performance Report (APR) data. Methods: This study included 6,309 participants who enrolled and received services in the Part C, Babies Can't Wait (BCW) program. A Pearson's correlation analysis was used to assess if there was an association between age at enrollment and improved child outcome score. One-way analysis of variance (ANOVA) was used to test the variances within the age groups for equality. Bonferroni post hoc test was used to compare the mean child outcome score across the enrollment age groups. Results: A statistically significant inverse correlation was found between enrollment age and improved child outcome score at 3 years of age. One-way ANOVA showed that the variances within the enrollment age groups were equal while the mean child outcome scores were not. Bonferroni post hoc test revealed that the mean child outcome score in the enrollment age group 0 to ≤ 6 months was significantly higher than the other age groups. Conclusions: Significantly better child outcomes were associated with enrollment in early intervention services before 6 months of age.